Penurunan Nilai TDS Pada Air Laut Menggunakan Destilasi Sederhana - Muliyadi Muliyadi; Idayani Sangadjisowohy (Poltekkes Kemenkes Padang, 2022)
Sea water pollution can cause direct and indirect health impacts. Environmental problems, water pollution problems in big cities in Indonesia, have shown quite serious symptoms. The purpose of this study was to determine the ability of the distillation method to reduce Total Dissolved Solid in seawater. This research method is a simple experimental design with a post test only group control design, carried out in the chemistry laboratory of the Ternate Health Polytechnic, with a simple distillation apparatus, 10 liters of seawater samples are used in each test. The Kolmogorov-Smirnov test was conducted to test the difference in TDS values ​​before and before distillation. There is a significant difference in the value of Salinity before and before distillation with the value of Sig. (2-tailed) it is known that 0.00 There is a significant difference in the TDS value before and before distillation with the Sig value. (2-tailed) is known to be 0.00. Simple distillation can reduce the pollutant load of TDS in seawater so that it can turn seawater into fresh water. Based on these results, it is hoped that further research will not only test TDS but also be able to test BOD and DO in seawater.